AUDIT DELAY IN COAL MINING FIRMS: THE ROLE OF PROFITABILITY, AUDIT OPINION, AND AUDITOR REPUTATION - Makkasau, Muhammad Bachtiar Makkasau; Usman, Asri; Rasyid, Syarifuddin (Akrual: Jurnal Bisnis dan Akuntansi Kontemporer, 2025)
This study aims to analyze the effect of profitability, Audit Opinion and KAP Reputation on disclosure Audit Delays in coal sector mining companies listed on the Indonesia Stock Exchange for the 2017-2021 period. This research is based on research methods, this research is ex-post facto research. ex-post research which is also known as causal comparative research is a systematic empirical investigation, while data collection is carried out by means of documentation on coal sector mining company documents listed on the Indonesia Stock Exchange for the 2017-2021 period. The results of this study indicate that: (1) Based on the results of partial testing, profitability, audit opinion and KAP reputation each have a significant effect on audit delay. (2) profitability, audit opinion and KAP reputation simultaneously have a significant effect on audit delay.